Розроблення комплексного підходу до підвищення міцності зварних оболонкових елементів з високоміцних сталей - Палаш, Роман; Назар, Ігор (КІНПАТРІ ЛТД, 2013)
The research of the complex of factors that affect technological strength and serviceability of welded joints in shell elements made of high-strength steels. Studied the interdependence of factorgroups of geometric, structural and thermodynamic character. Formed recommendations for selection of parameters of welding elements of this class.
Developing of integrated approach to increase durability of welded high-strength steel shell elements